PERAN PIMPINAN PESANTREN DALAM MENDISIPLINKAN PELAKSANAAN SHALAT BERJAMAAH SANTRI - Mukhlishah; Ibrohim, M.Ag., Dr. Iim; Murdani, Beni (LPPAIK Universitas Muhammadiyah Bandung, 2024)
Pesantren is an Islamic educational institution that has dormitories and aspires to produce the nation's successor students who have righteous creeds, true jurisprudence and noble morals and always become role models for the surrounding community. The formation of personality character that is emphasized in pesantren is a disciplined character, especially in the discipline of worship. The worship that gets the most attention from the leade pesantren is congregational prayer, because congregational prayer teaches the value of obedience and discipline while teaching the value of togetherness with others. Currently, the character of student discipline, especially in the discipline of congregational prayer, is less than optimal. Based on the observations of previous researchers at the Pesantren Kampung Quran Learning Center, there are still students who are not disciplined in carrying out congregational prayer activities such as not participating in congregational prayer activities on time. The initial findings when students are not disciplined in carrying out congregational prayer activities will have an impact on other activities such as teaching and learning activities in class, devotional work activities and Quran halaqa activities become undisciplined and students become less obedient to the rules of pesantren order. This is because prayer is the core of a Muslim's life activities, so if the prayer is good, then the life is good, but if the prayer is not good, then the life is not good. This is the background of researchers to conduct research at the Pesantren Kampung Quran Learning Center with the research title